2008
DOI: 10.1128/iai.01572-07
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Immunization with Porphyromonas gingivalis Outer Membrane Protein Decreases P. gingivalis -Induced Atherosclerosis and Inflammation in Spontaneously Hyperlipidemic Mice

Abstract: Porphyromonas gingivalis has been shown to accelerate atherosclerotic lesion development in hyperlipidemic animals. We assessed the potential of a nasal vaccine against P. gingivalis infection for the prevention of atherosclerosis. Apolipoprotein E-deficient spontaneously hyperlipidemic (Apoe shl ) mice were nasally immunized with the 40-kDa outer membrane protein (OMP) of P. gingivalis plus cholera toxin (CT) as adjuvant and then challenged intravenously with P. gingivalis strain 381. The animals were euthani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 59 publications
(52 reference statements)
1
65
0
Order By: Relevance
“…12,13 This organism promotes platelet aggregation, 14 foam cell formation, 15 and the development of atheromas in experimental animal models. [16][17][18][19] The following issues are discussed in this review:…”
Section: Introductionmentioning
confidence: 99%
“…12,13 This organism promotes platelet aggregation, 14 foam cell formation, 15 and the development of atheromas in experimental animal models. [16][17][18][19] The following issues are discussed in this review:…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in previous studies, we have demonstrated that nasal immunization with 40k-OMP plus cholera toxin (CT) or non-toxic chimeric enterotoxin (mCTA/LTB) elicited 40k-OMP-specific secretory immunoglobulin A (IgA) and IgG antibodies (Abs) in both saliva and serum, which inhibited the coaggregation activity of P. gingivalis, thus reducing alveolar bone loss (15)(16)(17)(18). Furthermore, when apolipoprotein E-deficient spontaneously hyperlipidemic mice were immunized intranasally with 40k-OMP plus CT before infection with P. gingivalis, atherosclerotic plaque deposition in the aortic sinus was significantly reduced (19). These studies suggest that 40k-OMP may be an effective vaccine antigen (Ag) for prevention of P. gingivalis infection.…”
Section: Introductionmentioning
confidence: 99%
“…These studies led us to predict that there might be some differences in the effect of atherogenic diet on atherosclerosis susceptibility between congenic SHL mice and apoE-/-mice. A few nutritional studies utilizing these three lines of congenic SHL mice have been reported 13,14) . From these considerations, the present experiment was carried out to determine experimental period and the adequate atherogenic diet composition such as dietary level of cholesterol and different type of oils, and AIN basal diets to induce reasonable atherosclerotic lesions for nutritional atherosclerosis studies using B6.KOR-Apoe shl mice.…”
Section: Introductionmentioning
confidence: 99%